Design and Characterization of Low-Cost Sensors for Air Quality Monitoring System - Rumantri, R.; N. Khakim, M. Y.; Iskandar, I. (Jurnal Pendidikan IPA Indonesia, 2018)
In this study, low-cost sensors for air quality monitoring system have been characterized and designed. These sensors are applied in a monitoring system and installed at Sriwijaya University, which is vulnerable to the impacts of forest fires in the surrounding area. This monitoring system will provide information especially for the university community to determine the level of air quality on campus. In this research the researchers focussed on the characterization and design of system sensor that aimed to get the best configuration of low-cost sensors namely MQ-7, Sharp GP2Y1010AU0F and own-designed smoke sensor to have high reliability and effectiveness to be applied to monitoring systems. The test results showed that the sensors have good response and sensitivity. Therefore, it can be applied to the monitoring system to provide information about the level of particle concentration, carbon monoxide and smoke which meet the needs of low-cost monitoring systems.